2016
DOI: 10.1103/physrevb.93.121402
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity limits structural superlubricity in large contacts

Abstract: Geometrically imposed force cancellations lead to ultra-low friction between rigid incommensurate crystalline asperities. Elastic deformations may avert this cancellation but are difficult to treat analytically in finite and 3D systems. We use atomic-scale simulations to show that elasticity affects the friction only after the contact radius a exceeds a characteristic length set by the core width of interfacial dislocations bcore. As a increases past bcore, the frictional stress for both incommensurate and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 44 publications
7
75
1
Order By: Relevance
“…More recently we used a Green's function approach 19,20 to capture the elastic response of a semi-infinite substrate while following individual atoms in contacts up to 2048 atoms across. 21 The results confirmed Hurtado and Kim's model for identical crystal surfaces, including the a −1/2 scaling at intermediate scales and the saturation of τ fric at large scales. The dimensionless control parameter is the ratio a/b core where b core is the width of an interfacial dislocation.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…More recently we used a Green's function approach 19,20 to capture the elastic response of a semi-infinite substrate while following individual atoms in contacts up to 2048 atoms across. 21 The results confirmed Hurtado and Kim's model for identical crystal surfaces, including the a −1/2 scaling at intermediate scales and the saturation of τ fric at large scales. The dimensionless control parameter is the ratio a/b core where b core is the width of an interfacial dislocation.…”
Section: Introductionsupporting
confidence: 82%
“…However we found that dislocations can allow large contacts to lock, yielding a value of τ fric ≈ τ Peierls equal to that for very large identical, aligned crystals. 21 Hurtado and Kim's model and previous numerical tests considered systems with a constant local shear stress τ max and simplified the problem by removing the local curvature of the surface. At high loads and for nonadhesive surfaces atomistic simulations show that the local frictional stress is proportional to pressure, [25][26][27] yielding a constant local friction coefficient α = τ max /p rather than a constant shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing scales, structural superlubricity would disappear due to the deformation of the slider leading to a local commensuration with the substrate lattice . Shorter critical length scale in 2D contact was expected due to the larger contribution of high‐friction boundaries compared to that in 1D systems . Recently, the effects of elasticity on superlubricity predicted theoretically have been partially confirmed by experiments .…”
Section: Structural Superlubricity In Homogeneous Interfacesmentioning
confidence: 89%
“…For (quasi‐)1D system, Ma et al proposed a parameter‐free analytical model to estimate critical length above which superlubricity disappears . With increasing scales, structural superlubricity would disappear due to the deformation of the slider leading to a local commensuration with the substrate lattice . Shorter critical length scale in 2D contact was expected due to the larger contribution of high‐friction boundaries compared to that in 1D systems .…”
Section: Structural Superlubricity In Homogeneous Interfacesmentioning
confidence: 99%
“…Indeed, we know from theory and simulation [74][75][76] that even in clean wearless friction experiments with perfect atomic structures, superlubricity at large scales may, for example, surrender due to the soft elastic strain deformations of contacting systems.…”
Section: Contact Area Dependence and New Perspectives In Superlubricitymentioning
confidence: 99%